THE APPLICATION OF WIND BLOWS GAME TO DEVELOP STUDENTS’ VOCABULARY AT THE EIGHTH GRADE IN MTS MA’ARIF BOLAROMANG - Amelia, Reski; Amin, Bahrun; Mahmudah, Dzur Rif'ah (FKIP Unismuh Makassar, 2021)
The research aims to find out the application of Wind Blows Game to develop students’ vocabulary at the eighth grade in MTs Ma’arif Bolaromang. This research was conducted in a pre-experimental using a quantitative approach. To collect the data from the students, the researcher was use test (vocabulary test). The sample was selected by using total sampling because the researcher took one class at the eighth grade in MTs Ma’arif Bolaromang. The sample in this research was 20 students. The research found that there was a significant difference between students' pre-test and post-test scores. The students' mean score before treatment was 47.75, but it improved to 78.75 after applying Wind Blows Game. While the students' mean score in the term of verb before treatment was 52, it improved to 76 after treatment. It's the same with the students' mean score in the term of noun, which was 43.5 before treatment and 81.5 after applied Wind Blows Game. Furthermore, t-test analysis showed that t-test value was bigger than t-table, indicating that students' vocabulary totally (12.03>1.729), verb (6.99>1.729), and noun (10.57>1.729) were all higher than t-table. As a result, the Null Hypothesis (H0) was rejected and the Alternative Hypothesis (H1) was accepted as the research hypothesis. It shows that Wind Blows Game was successful in developing students' verb and noun vocabulary